2008
DOI: 10.2337/db07-1750
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Estrogen Receptor Is Crucial for Resveratrol-Stimulating Muscular Glucose Uptake via Both Insulin-Dependent and -Independent Pathways

Abstract: OBJECTIVE-Estradiol (E 2 ) is known to modulate insulin sensitivity and, consequently, glucose homeostasis. Resveratrol (RSV), an agonist of estrogen receptor (ER), has exerted antihyperglycemic effects in streptozotocin-induced type 1 diabetic rats in our previous study and was also shown to improve insulin resistance in other reports. However, it remains unknown whether activation of ER is involved in the metabolic effects of RSV via insulin-dependent and -independent mechanisms. RESEARCH DESIGN AND METHODS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
96
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(104 citation statements)
references
References 36 publications
8
96
0
Order By: Relevance
“…The later result is in accordance with our study result; in our study also HACE had increased GLUT4 contents of muscular tissue culture model, C2C12 myotubes that this effect was dosedependent (see results). Also Deng et al [34] have shown that resveratrol, an ingredient of Polygonum cuspidatum and red wine did enhance glucose uptake and GLUT4 movement to the CM in C2C12 myotubes. However, other in vivo, ex vivo studies and human trials which have been explored antidiabetic effect or mechanism by which cinnamon exert antidiabetic effect all are in accordance with our study results [14,16,[35][36][37][38].…”
Section: Resultsmentioning
confidence: 94%
“…The later result is in accordance with our study result; in our study also HACE had increased GLUT4 contents of muscular tissue culture model, C2C12 myotubes that this effect was dosedependent (see results). Also Deng et al [34] have shown that resveratrol, an ingredient of Polygonum cuspidatum and red wine did enhance glucose uptake and GLUT4 movement to the CM in C2C12 myotubes. However, other in vivo, ex vivo studies and human trials which have been explored antidiabetic effect or mechanism by which cinnamon exert antidiabetic effect all are in accordance with our study results [14,16,[35][36][37][38].…”
Section: Resultsmentioning
confidence: 94%
“…However, changes in inflammation levels and myocardial insulin signaling pathway require further investigation. Additionally, nutrients like resveratrol improve insulin sensitivity 19,23 and reduce inflammation and incidence of coronary diseases 16 . Thus, the study hypothesis was that resveratrol supplementation could benefit the myocardial insulin signaling pathway of obese rats.…”
Section: Discussionmentioning
confidence: 99%
“…The resveratrol has also been shown to benefit the insulin signaling pathway 21,23 . Resveratrol supplementation increased IRS1 and Akt phosphorylation in the liver and soleus muscle of insulin-resistant rats, and reduced blood glucose and insulin 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Data confirmed the effect of RSV on oxidative stress reduction in skeletal muscle (Chang et al., 2014). It is noteworthy that RSV affects skeletal muscles by increasing GLUT4 expression and augmenting intracellular glucose transport (Deng, Hsieh, Huang, Lu, & Hung, 2008). RSV was also found to reduce gluconeogenesis activity and increase liver glycogenesis, which leads to hepatic glucose output reduction.…”
Section: Resveratrol and Diseasesmentioning
confidence: 99%
“…Actually, activation of these targets by RSV as a drug led to cellular and enzymatic phenomena including decreased lipid accumulation, inflammation, and oxidative damage in liver, muscle, and adipocyte tissues and finally led to insulin action improvement in type 2 diabetes (Figure 5). However, another possible mechanism suggested in different studies including increased phosphorylation of insulin receptor, IRS‐1 expression, and phosphorylation of Akt (Chen, Li et al., 2012; Deng et al., 2008). In another in vivo study conducted by Cheng et al., it has been shown that resveratrol promoted nuclear factor erythroid 2‐related factor‐2 (Nrf2) phosphorylation, in the pancreas of methylglyoxal‐treated mice.…”
Section: Resveratrol and Diseasesmentioning
confidence: 99%